Chromosome 9p21 primary open‐angle glaucoma susceptibility locus: a review. (30th October 2013) - Ng, Soo Khai; Casson, Robert J; Burdon, Kathryn P; Craig, Jamie E
Abstract Primary open‐angle glaucoma (POAG) is a genetically complex disease. Genome‐wide association study (GWAS) is a particularly useful tool in the search for genetic contributions to glaucoma. Recently, chromosome 9p21 has become a major focus of research endeavour, with multiple genome‐wide association studies suggesting associations to POAG. Herein, we provide a review of the chromosome 9p21 susceptibility locus as a risk factor for POAG.